Visual Content Analysis of STEM-Related Content in Indonesian Vocational High Schools Biology Textbooks - Bevo Wahono; Ima Masafatus Sholihah; Erlia Narulita (Journal of Science Learning, 2023)
This research aims to analyze the characteristics of STEM-related visual content in Indonesian Vocational High School biology textbooks. Biology textbooks have been adapted to the latest scientific and technological advances and curriculum demands and declared feasible. However, some distributed biology textbooks in Indonesia may need to be improved and have various areas for improvement and problems. This study used NVivo to perform a descriptive statistic comprising 197 visual samples from the two biology textbooks. The results have shown that the type of "sketch comics" is the most common at 30.5%. In addition, the type of "representation" is the most visual function found in this study, with 44.7%. The study has seen all of the STEM domains appearing in biology textbooks. Most of the STEM domain with visual content relates to scientific content. Other components discussed in detail and essential to the development of the student learning unit are schematic views displaying biological processes and representation functions. Therefore, the authors of biology textbooks need to consider the types and functions of visual content holistically, particularly regarding the context of the topics that can represent effective visual content and develop student understanding